Do the Geneva Conventions matter? / edited by Matthew Evangelista and Nina Tannenwald. - Evangelista, Matthew, 1958-; Tannenwald, Nina (Oxford University Press, 2017)
Publisher's description: The Geneva Conventions are the best-known and longest-established laws governing warfare, but what difference do they make to how states engage in armed conflict? Since the start of the 'War on Terror' with 9/11, these protocols have increasingly been incorporated into public discussion. We have entered an era where contemporary wars often involve terrorism and guerrilla tactics, but how have the rules that were designed for more conventional forms of interstate violence adjusted? [This book analyzes] the laws that govern warfare and a more specific investigation relating to state practice. [The authors] convey the extent and conditions that symbolic or 'ritual' compliance translates into actual compliance on the battlefield by looking at important studies across history. To name a few, they navigate through the Algerian War for independence from France in the 1950s and 1960s; the US wars in Korea, Vietnam, Iraq, and Afghanistan; Iranian and Israeli approaches to the laws of war; and the legal obligations of private security firms and peacekeeping forces. [This] work adds to the law and society literature in sociology, the constructivist literature in international relations, and legal scholarship on 'internalization.' [This book] gives insight into how the Geneva regime has constrained guerrilla warfare and terrorism and the factors that affect protect human rights in wartime.